Business elites in Panama: Sources of power and state capture - Julián Cárdenas; Francisco Javier Robles Rivera (United Nations Research Institute for Social Development (UNRISD), 2020)
A well-established line of academic inquiry argues that state capture emerges in contexts of weak governance institutions. However, Panama is an outlier case featuring high levels of state capture despite strong governance institutions. To better understand state capture in Panama, this paper investigates the sources from which business elites draw their power-income control, business cohesion, political campaign contributions and revolving doors. Results show that state capture arose in Panama along with high income concentration among top elites, cohesion among a small cluster of family business groups, big businesses coordinating their electoral contributions, and appointments of businesspeople to strategic government positions. In closing, we suggest possible avenues of research to continue deciphering state capture, and provide some policy recommendations to reduce state capture in Panama.
Keywords: 330; Business cohesion; business groups; campaign contributions; Latin America; network analysis; revolving doors